THE ROLE OF ENERGY STORAGE TECHNOLOGIES IN DECARBONIZING ENERGY SECTOR - Vucic, Vlastimir (The European Journal of Applied Economics, 2025)
A mounting requirement to increase the capacity for storing the energy generated from renewables drives the energy storage sector. However, there is no one-size-fits-all approach when it comes to storing energy. Relevant to the recent growth in energy storage are Battery Energy Storage Systems (BESS), particularly those based on lithium-ion. During the last decade, the cost of lithium-ion batteries has decreased by more than 90%, with battery cell prices estimated to continue this downward trend, adding to the attractiveness of energy storage. Major countries retain focus on lithium-ion batteries’ supply chain, following their ambitions to build local manufacturing, gain international advantage, attract investment, and create jobs. Another crucial concern is linked to raw material supplies. Challenges for developing countries include a lack of skilled human resources and adequate monitoring and control equipment, underdeveloped or non-existent grid infrastructure, insufficient generation capacity, poor supply security, etc. Energy storage can boost reliability, which is vital when shifting from thermal projects to hybrid ones. Hence, this research investigates the general attitude over energy storage adoption and widespread use, including economic constraints, industry acceptance, contemporary technology, and regulatory barriers.